1994
DOI: 10.1093/oxfordjournals.jae.a036794
|View full text |Cite
|
Sign up to set email alerts
|

Land Tenure Reform in East Africa: Good, Bad or Unimportant?1

Abstract: Theoretical arguments lead to the conclusion that there should be more land-secured credit, more investment, a more active land market, and more inequality of land in a community under freehold tenure compared with one in which the state owns and allocates the land. Detailed evidence from two communities in Kenya and Tanzania suggests that none of these conclusions holds because the stated policy differences do not in fact cause the land markets to perform differently in the two countries. These results are in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
68
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(73 citation statements)
references
References 12 publications
5
68
0
Order By: Relevance
“…Other research in rural areas, especially in sub-Saharan Africa, has detected little impact of titling on investment, land productivity and access to credit (Pinckney and Kimuyu 1994;Place and Migot-Adholla 1998;Place and Otsuka 2002;Brasselle et al 2002). These authors argue that the weak effects of titling show that informal land tenure arrangements can provide considerable investment security, especially in stable communities.…”
Section: Informal Capital and Property Rightsmentioning
confidence: 98%
“…Other research in rural areas, especially in sub-Saharan Africa, has detected little impact of titling on investment, land productivity and access to credit (Pinckney and Kimuyu 1994;Place and Migot-Adholla 1998;Place and Otsuka 2002;Brasselle et al 2002). These authors argue that the weak effects of titling show that informal land tenure arrangements can provide considerable investment security, especially in stable communities.…”
Section: Informal Capital and Property Rightsmentioning
confidence: 98%
“…Bruce, 1988;Place and Hazell, 1993;Sjaastad and Bromley, 1997;Brasselle et al, 2002;Otsuka et al, 2003). Finally, there are also studies that have shown that tenure security is not important for land conservation (Migot-Adholla et al, 1991Place and Hazell, 1993;Pinckney and Kimuyu, 1994), or that highly individualized rights to land are more important for long-term rather than short-term investments (Place and Otsuka, 2000, Place and Swallow, 2000, Gebremedhin and Swinton, 2003.…”
Section: Empirical Evidencementioning
confidence: 99%
“…In terms of definition, most studies focus on security of tenure rather than transferability. Many studies use binary dummies to capture security in terms of having a land title (see for instance Roth et al, 1994aRoth et al, , 1994bPinckney and Kimuyu, 1994;Migot-Adholla et al, 1994;Shiferaw and Holden, 1999;Place and Otsuka, 2002), while Gebremedhin and Swinton (2003) take a continuum of expected rights. Brasselle et al (2002), Otsuka et al (2003) and Gavian and Fafchamps (1996) have focused on the mode of land acquisition, such as purchase, borrow, or gift.…”
Section: Empirical Evidencementioning
confidence: 99%
“…If the costs of first-time registration and up-to-date registry records are not commensurate with the benefits of land registration, it can be difficult to carry out either of these steps. A combination of these issues has often limited the effectiveness and reach of land registration in many African contexts (Pinckney and Kimuyu 1994;Bruce and Migot-Adholla 1994;Jacoby and Minten 2007), so it is important to determine how Ethiopia managed these problems.…”
mentioning
confidence: 99%